GRPr Theranostics: Current Status of Imaging and Therapy using GRPr Targeting Radiopharmaceuticals - Kurth, Jens; Potratz, Madlin; Heuschkel, Martin; Krause, Bernd J; Schwarzenböck, Sarah Marie (Nuklearmedizin - NuclearMedicine, 2022)
Addressing molecular targets, that are overexpressed by various tumor entities, using radiolabeled molecules for a combined diagnostic and therapeutic (theranostic) approach is of increasing interest in oncology. The gastrin-releasing peptide receptor (GRPr), which is part of the bombesin family, has shown to be overexpressed in a variety of tumors, therefore, serving as a promising target for those theranostic applications. A large amount of differently radiolabeled bombesin derivatives addressing the GRPr have been evaluated in the preclinical as well as clinical setting showing fast blood clearance and urinary excretion with selective GRPr-binding. Most of the available studies on GRPr-targeted imaging and therapy have evaluated the theranostic approach in prostate and breast cancer applying bombesin derivatives tagged with the predominantly used theranostic pair of 68Ga/177Lu which is the focus of this review.
Keywords: Theranostika; Gastrin-releasing peptid receptor; Bombesin; Prostatakarzinom; Brustkrebs; Gallium-68/ Lutetium-177